2011
DOI: 10.5539/jas.v3n3p246
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Marketing Channel and Pricing System of Cashewnuts in the North Central of Nigeria

Abstract: This study examined the marketing channel and pricing system of cashew nut in the eastern part of Kogi state. A total of 180 respondents were randomly selected from 3 market zones of the area. Data collected were analyzed using descriptive statistics. The result from the study indicated a unidirectional movement of cashew nut from the producers to the final consumers. 14.67% of the marketers were involved in retailing and small scale business, 38.33% were bulk assemblers and 20.00% of them engaged in wholesale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Other challenges were high cost of transportation 3.86, bad road with a mean score of 3.86, high purchasing price with an average score of 3.44, theft with a mean score of 3.84, levies on shop/site with a mean score of 3.05 and inadequate capital with an average of 2.71. Adejo et al (2011) and Akintonde et al (2013) agree with these findings.…”
Section: Constraints Militating Against Cashew Nut Marketing In the S...supporting
confidence: 52%
See 1 more Smart Citation
“…Other challenges were high cost of transportation 3.86, bad road with a mean score of 3.86, high purchasing price with an average score of 3.44, theft with a mean score of 3.84, levies on shop/site with a mean score of 3.05 and inadequate capital with an average of 2.71. Adejo et al (2011) and Akintonde et al (2013) agree with these findings.…”
Section: Constraints Militating Against Cashew Nut Marketing In the S...supporting
confidence: 52%
“…Inadequate information on the marketing of some food crops is a major factor to the problem of unorganized food commodity markets in Nigeria (Adejo et al, 2011). The authors observed that cashew nut marketing is highly affected by price instability due to seasonality nature of the crops production coupled with unavailability of storage and processing equipment.…”
Section: Introductionmentioning
confidence: 99%
“…The return on investment of cashew ranges between 30 to 40 percent within 3-5 years of cultivation [3]; this shows that cashew farming is a profitable business. The average yield of the nuts of a mature cashew tree ranges from 7-11kg per annum [4]. The most relevant characteristics of cashew are sizes of the nut, tree height, apple colour, resistance to disease and nut yield [5].…”
Section: Introductionmentioning
confidence: 99%
“…Traits of importance in cashew are nut size, tree height, the colour of apple, disease resistance and nut yield (Aliyu et. al., 2008) with a mature tree producing a yield within the range of 7-11 kg per annum (Adejo et. al., 2011).…”
Section: Introductionmentioning
confidence: 99%